Materials science in microelectronics - Machlin, E. S. (Elsevier, 2005)
The subject matter of thin-films which play a key role in microelectronics divides naturally into two headings: the processing / structure relationship, and the structure / properties relationship. Part II of 'Materials Science in Microelectronics' focuses on the latter of these relationships, examining the effect of structure on the following: Electrical properties Magnetic properties Optical properties Mechanical properties Mass transport properties Interface and junction properties Defects and properties * Captures the importance of thin films to microelectronic development * Examines the cause / effect relationship of structure on thin film properties.